Development of a real-time Power quality monitoring Instrument for Detection and Classification of Disturbances in a Single-phase Power System - Radil, Tomas (2009)
In this paper, the initial development stages of a power quality monitoring instrument are described. The paper is focused on new algorithms developed for real-time detection and classification of power quality disturbances. The developed algorithms aim to cover a wide range of disturbances that may occur in a power system and that may differ in their characteristics (e.g. magnitude or duration). The algorithms were tested using both simulated disturbances and disturbances measured using a specifically designed measuring system.